Media ownership and control: law, economics and policy in an Indian and international context (Hart studies in competition law) - Rab, Suzanne; Sprague, Alison (Hart studies in competition law, 2014)
As academics, lawyers, businesses, regulators and policy-makers in India cast a glance at the international experience, this book examines the legal, economic and policy issues relating to regulation of ownership and control of media markets.